Surgical and Pathological Changes after Radiofrequency Ablation of Thyroid Nodules. (21st July 2015) - Dobrinja, Chiara; Bernardi, Stella; Fabris, Bruno; Eramo, Rita; Makovac, Petra; Bazzocchi, Gabriele; Piscopello, Lanfranco; Barro, Enrica; de Manzini, Nicolò; Bonazza, Deborah; Pinamonti, Maurizio; Zanconati, Fabrizio; et al.
Abstract : Background . Radiofrequency ablation (RFA) has been recently advocated as an effective technique for the treatment of symptomatic benign thyroid nodules. It is not known to what extent it may affect any subsequent thyroid surgery and/or histological diagnosis. Materials and Methods . RFA was performed on 64 symptomatic Thy2 nodules (benign nodules) and 6 symptomatic Thy3 nodules (follicular lesions/follicular neoplasms). Two Thy3 nodules regrew after the procedure, and these patients accepted to undergo a total thyroidectomy. Here we present how RFA has affected the operation and the final pathological features of the surgically removed nodules. Results and Conclusions . RFA is effective for the treatment of Thy2 nodules, but it should not be recommended as first-line therapy for the treatment of Thy3 nodules (irrespective of their mutational status), as it delays surgery in case of malignancy. Moreover, it is unknown whether RFA might promote residual tumor progression or neoplastic progression of Thy3 lesions. Nevertheless, here we show for the first time that one session of RFA does not affect subsequent thyroid surgery and/or histological diagnosis.